1993
DOI: 10.1002/ajh.2830430213
|View full text |Cite
|
Sign up to set email alerts
|

Adult‐onset cyclic neutropenia responsive to cyclosporine therapy in a patient with ankylosing spondylitis

Abstract: A 45-year-old female with a long history of HLA-B27-positive ankylosing spondylitis and ulcerative colitis developed cyclic neutropenia. She was hospitalized for high fever during each of three consecutive episodes of absolute neutropenia. On the third hospitalization, granulocyte-colony-stimulating factor (G-CSF), 5 micrograms/kg/day, was given by subcutaneous injection and resulted in an increase of absolute neutrophil count from 0 to 2.2 x 10(9)/liter and an associated decrease of platelet count and hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Thus far, only two adult cases of cyclic AIN have been reported in the literature. Storek and coworkers described the first case of secondary cyclic AIN treated with cyclosporine in a patient with ankylosing spondylitis and ulcerative colitis. More recently, another team described a young woman with AIN with cyclic oscillation of the neutrophil count after steroid treatment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, only two adult cases of cyclic AIN have been reported in the literature. Storek and coworkers described the first case of secondary cyclic AIN treated with cyclosporine in a patient with ankylosing spondylitis and ulcerative colitis. More recently, another team described a young woman with AIN with cyclic oscillation of the neutrophil count after steroid treatment .…”
Section: Discussionmentioning
confidence: 99%
“…The production of these antibodies results in neutropenia because they precipitate peripheral destruction of neutrophils through agglutination or phagocytosis . Some cases of AIN have been reported to show cyclic fluctuation of neutrophil counts . However, there have been no previous reports of cyclic AIN confirmed by the cyclic production of anti‐neutrophil antibodies.…”
mentioning
confidence: 99%
“…It has been reported that cytokine administration to patients with a history of autoimmune disease induces new symptoms or aggravates their original symptoms [1,3,10]. G-CSF has been reported to activate the symptoms of idiopathic iridocyclitis [7] and autoimmune diseases such as ankylosing spondylitis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Flare‐ups of autoimmune disease are also reported. An exacerbation of ankylosing spondylitis and ulcerative colitis was observed in a patient with cyclic neutropenia who received G‐CSF, 12 and marginal keratitis, uveitis, and acute iritis have been reported in G‐CSF–mobilized PBSC donors 13,14 . Granulocyte‐monocyte CSF has caused worsening of rheumatoid arthritis 15 and abnormalities of thyroid function in 2 of 25 patients with cancer who received it.…”
Section: Acute Side Effects Associated With G‐csf Administrationmentioning
confidence: 99%